Intersecting Linear Light Strands: a Particle Explanation for the Fresnel Central Spot - Dutt, Srin (International Research Journal of Multidisciplinary Technovation, 2022)
The Fresnel central spot in a shadow, theorized to be generated from wave interference, has given strong support for wave models of light. Using extended exposure macro imaging in various media, the shadow is shown to be more complex with multiple lines of light intersecting in the center. Using the particle concept of discrete light strands perpendicularly reflecting from a diffraction source, these observations can be more accurately explained. Another quantized aspect of light is shown where linear light strands become rings when an energy threshold is reached.